Floral structure, development of the gynoecium, and embryology in Schinopsis balansae Engler (Anacardiaceae), with particular reference to aporogamy - Gonzalez, Ana Maria (2016)
Premise of research. The Apodanthaceae, the only parasitic lineage within the order Cucurbitales, comprises one species of Apodanthes and 12 species of Pilostyles, parasitizing Salicaceae, and legume stems, respectively. All species are achlorophyllous and holoparasitic, with a mycelium-like endophyte. Although flowers, fruits, and seeds are the only organs available for morphological and taxonomic studies, floral development has not been recorded, and morphoanatomical observations in the family are scarce. Given the position of the Apodanthaceae as the earliest-diverging group within the Cucurbitales, their floral characters allow a reevaluation of the apomorphies for the order, as well as those features specific to the Apodanthaceae, likely linked to their holoparasitic lifestyle. Methodology. We used LM and SEM protocols to record all developmental stages from early floral initiation through fruit and seed ripening of Pilostyles boyacensis, a species inhabiting dry Andean forests. Pivotal results. Floral development occurs completely inside the host. Perianth organs are formed in a spiral. Staminate flowers develop a central column with a basal nectary disk before synandrium formation. A ring of vesicular hairs forms above the synandrium. Carpellate flowers lack vesicular hairs. The funicle is schizogenous, and the chalazal exotesta forms an elaiosome likely related to ant dispersal; these traits are here proposed as apomorphic in Apodanthaceae. Carpellate flowers are more frequent than staminate flowers (74% vs. 20%). Additionally, chimeric, half-staminate, and half-carpellate flowers occur in 6% of the total of dissected flowers (n = 276). Conclusions. The Apodanthaceae shares with the remaining Cucurbitales polysymmetric flowers; free perianth organs with stomata; simultaneous microsporogenesis; anatropous, bitegmic ovules; chalazal functional megaspore; Polygonum-type embryo sac; exotestal seed coat; and nuclear endosperm. Chimeric half-staminate and half-carpellate flowers indicate a more labile sex determination in Apodanthaceae, whose flowers are often described as unisexual. Athecal stamens lacking fibrous endothecium, carpels distally fused, tenuinucellate ovules, berries with persistent perianth, schizogenous funicle, and seeds with elaiosome are apomorphic to Apodanthaceae. The latter two traits are described in detail for the first time in the family.